Extraction of saponins from Vietnamese soapnuts for application to washing fabrics - Nguyen, Ngoc Thang; Ngo, Ha Thanh (JST: Engineering And Technology For Sustainable Development, 2021)
In this paper, the aqueous extraction of saponins from Vietnamese soapnuts and evaluation of its washing effectiveness for cotton fabrics have been presented. The saponin content in soapnut extract was 40.82 g/l. The functional groups of saponin compounds refined from soapnut extract were confirmed by FTIR analysis. The washing performance of this natural surfactant has been evaluated by a bleached cotton woven fabric and 10 fabric samples of K’s closet joint-stock company. Two washing options were designed: washing with soapnut solution and washing with soapnut solution then softening. The laundry effects were evaluated by performing the shrinkage (TCVN 1755:1986), the drape (NF G07-109), the horizontal wicking (AATCC 198-2011) and the whiteness of the fabric (TCVN 5236:2002). The analysis results showed the washed fabrics using the first washing option had the shrinkage, drape coefficient and horizontal wicking values higher than those of the washed fabrics using the second washing option. The whiteness and yellowness of the washed fabrics were lightly influenced by the natural deep brown color of saponin in the soapnut extract. The successful application of the saponin extracted from Vietnamese soapnuts as a green laundry agent for washing fabrics could make it very promising in the textile sustainable development.